Microbial surfactants: A journey from fundamentals to recent advances - Pardhi, Dimple S.; Panchal, Rakeshkumar R.; Raval, Vikram H.; Joshi, Rushikesh G.; Poczai, Peter; Almalki, Waleed H.; Rajput, Kiransinh N. (Frontiers in Microbiology, 2022)
Microbial surfactants are amphiphilic surface-active compounds that help lower surface and interfacial tensions by accumulating between two fluid phases. Biosurfactants are broadly classified based on their chemical composition and molecular weight. They exhibit different fundamental properties like surface tension reduction, emulsification, adsorption, micelle formation, etc. Microbial genera like Bacillus spp., Pseudomonas spp., Candida spp., and Pseudozyma spp. are studied extensively for their production. The type of biosurfactant produced is reliant on the substrate utilized and the pathway pursued by the generating microorganisms. Biodegradability, low toxicity, bioavailability, specificity of action, structural diversity, and effectiveness under harsh conditions are some of the biosurfactants' advantages over synthetic surfactants. Biosurfactants are physiologically essential molecules for the producer microbes, which provide antimicrobial, anti-adhesive, and antioxidant properties, as well as the ability to grasp substrates easily absorbed by cells in adverse conditions. Due to their useful qualities, biosurfactants are in high demand as a prospective product in industries such as petroleum, cosmetics, detergents, agriculture, medicine, and food. Biosurfactants are the most important natural biodegradable compounds used to replace synthetic surfactants in the global market for a cleaner and healthier sustainable environment.